2016
DOI: 10.1186/s40510-016-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three-dimensional stress distribution and displacement of naso-maxillary complex on application of forces using quad-helix and nickel titanium palatal expander 2 (NPE2): a FEM study

Abstract: BackgroundOur objectives are to analyse and to compare the stress distribution and displacement of the craniofacial structures, following the application of forces from quad-helix and Nickel Titanium Palatal Expander-2 (NPE2) using finite element analysis.MethodsThree-dimensional finite element models of young dried human skull, quad-helix appliance and NPE2 were constructed, and the initial activation of the expanders was stimulated to carry out the analysis and to evaluate the Von Misses stresses and displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Two systematic reviews have shown a positive influence of text messages on behavioural changes [ 8 ], and a significant association between the use of mobile technologies and the improvement in dental plaque control and gingival bleeding [ 9 ]. Previous studies proposed a system of active reminders for adolescents undergoing orthodontic treatment by weekly text messaging their parents [ 8 , 10 12 ], using WhatsApp chat room for sharing “selfies” of their smile [ 13 ], and using computer-based training to teach Fones brushing technique or modified Bass technique [ 14 ]. In addition, frequently used social media among young subjects, such as Instagram [ 15 ], or other digital platforms, such as YouTube [ 16 ], have shown to improve oral health knowledge among orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews have shown a positive influence of text messages on behavioural changes [ 8 ], and a significant association between the use of mobile technologies and the improvement in dental plaque control and gingival bleeding [ 9 ]. Previous studies proposed a system of active reminders for adolescents undergoing orthodontic treatment by weekly text messaging their parents [ 8 , 10 12 ], using WhatsApp chat room for sharing “selfies” of their smile [ 13 ], and using computer-based training to teach Fones brushing technique or modified Bass technique [ 14 ]. In addition, frequently used social media among young subjects, such as Instagram [ 15 ], or other digital platforms, such as YouTube [ 16 ], have shown to improve oral health knowledge among orthodontic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of FEM analysis may differ from the real-world scenario by up to 20%. 3,14,17 Passive self-ligating brackets (SLBs) are gaining popularity due to easier and faster ligation, reduced friction, adequate torque expression, and reduced overall treatment time. The gate or fourth wall retains the wire in the slot enabling ligation and tooth movement.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions for complex biomechanical questions can be obtained by using FEM. 14, 15 Unlike clinical experiments requiring patients or animals, FEM can be used to simulate treatment approaches and observe biomechanical responses. 16 Loading configuration, structure geometry, and material properties affect FEM reliability.…”
Section: Introductionmentioning
confidence: 99%
“…12 FEM is nearly similar to the clinical situation; however, the qualitative behavior of a dry skull doesn't mimic with a high level of exactness in the clinical circumstance. 13 It is conceivable to demonstrate the way that the permanent first molar moves distally and study the commitment effect of molar distalization such as flaring of anterior teeth due to the loss of anchorage the force impact craniofacial structures and a profile change in the lower third of the face. 14,15 FEM has several merits, such as (1) noninvasive technique; (2) theoretically, the definite value of applied stress at any point can be measured; (3) teeth and their supporting structures as well as the craniofacial bones can be simulated and mechanical properties of these structures can be assigned; (4) the applied force direction, magnitude, and application are easily modified to mimic the clinical situation, and (5) reproducibility does not affect the physical properties of relegated material.…”
Section: Introductionmentioning
confidence: 99%